Synthesis of Racemic and Enantiopure Forms of β-Carboline Alkaloid Brevicolline - Szabó, Tímea; Görür, Funda Lidya; Horváth, Simon; Volk, Balázs; Milen, Mátyás (Synthesis, 2022)
A new total synthesis of the pharmacologically active β-carboline alkaloid brevicolline is described. The new synthetic approach is based on a commercially available and inexpensive starting material and reagents leading to a practical synthesis of the racemic target molecule, the natural (S)-enantiomer, and its antipode. Initially, the construction of the β-carboline skeleton and functionalization at the C(4) position have been accomplished. The formation of dihydropyrrole structural unit was obtained as the result of an Au-catalyzed hydroamination reaction, which was followed by a reduction that led to the chiral intermediate. The synthetic route described here is developed to ensure the sustainable access of the racemic brevicolline in 11 steps with improved 48% overall yield compared to the previously reported methods.
Keywords: brevicolline; natural product; β-carboline; total synthesis; chiral chromatography